Pengaruh Model Kooperatif Group Investigation terhadap Keterampilan Menulis Teks Berita Siswa SMPN 1 Pariangan - Revi Hafizah; Farel Olva Zuve; Afnita Afnita; Dadi Satria (Universitas Muhammadiyah Magelang, 2026)
This study was motivated by the low level of students’ skills in writing news texts, particularly in organizing text structure, developing the 5W+1H elements, applying language rules, and using correct Indonesian spelling (EYD). The objectives of this study were to describe the news text writing skills of seventh-grade students of SMP Negeri 1 Pariangan without using the Group Investigation cooperative learning model, to describe the students’ news text writing skills using the model, and to analyze the effect of the model on students’ news text writing skills. This research employed a quantitative approach with a quasi-experimental method using a control-only group posttest design. The population consisted of all seventh-grade students of SMP Negeri 1 Pariangan in the 2025/2026 academic year totaling 51 students. The samples were selected using purposive sampling, consisting of 25 students in the control class and 26 students in the experimental class. Data were collected through a performance test on writing news texts based on four indicators: news text structure, elements of news text, language rules, and spelling (EYD). Data were analyzed using normality tests, homogeneity tests, and a t-test. The results showed that the average score of students’ news text writing skills without using the Group Investigation model was 69.5 (fair category), while the average score using the model was 75.96 (good category). The hypothesis testing showed that t count ”‹ >t table ”‹ (2.46 > 2.01). Therefore, it can be concluded that the Group Investigation cooperative learning model has a significant effect on the news text writing skills of seventh-grade students at SMP Negeri 1 Pariangan